2006
DOI: 10.1111/j.1460-9568.2006.05219.x
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin in microglia from frontal cortex is up‐regulated in schizophrenia: evidence for an inflammatory process?

Abstract: Schizophrenia is associated with a number of pathological changes, including alterations in levels of specific proteins. Calprotectin is a novel 36 kDa calcium-binding protein of the S100 family and appears to be a nonspecific marker of inflammation. Calprotectin has not previously been investigated in brain tissue. Samples of post-mortem brain tissue from Brodmann area 9 were obtained from prefrontal cortex from subjects with schizophrenia, bipolar affective disorder, major depression, and from controls. Calp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Inflammation may therefore be present in a subset of patients with schizophre nia, consistent with findings in grey matter in individuals with this disorder. 48,49 Limitations When interpreting our results some methodological limita tions should be kept in mind. First, we identified oligoden drocytes using a nonspecific histological stain, an approach used in several previous studies of this cell population.…”
Section: Discussionmentioning
confidence: 96%
“…Inflammation may therefore be present in a subset of patients with schizophre nia, consistent with findings in grey matter in individuals with this disorder. 48,49 Limitations When interpreting our results some methodological limita tions should be kept in mind. First, we identified oligoden drocytes using a nonspecific histological stain, an approach used in several previous studies of this cell population.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, in pathophysiological conditions when the redox potential of the extracellular fluids can vary greatly, the interaction of the drug with the target can be modified consequently. This is not so hypothetical since severe disorders like schizophrenia are frequently associated with neurodegenerative processes and inflammatory events [44][45][46]. In another context, food deprivation is recently shown to affect brain oxidation status in rat especially with a significant increase in H 2 O 2 production [47].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the protein and mRNA levels of the M2-related growth factor BDNF were significantly reduced in the frontal cortices of schizophrenia patients [27]. The protein expression levels of other microglial marker chemokines, S100A8/A9, were significantly higher in the dorsolateral prefrontal cortices of patients with schizophrenia [42]. Additionally, there were significantly more QUIN-immunoreactive microglial cells in the CA1 hippocampal subregions of schizophrenia patients.…”
Section: Schizophreniamentioning
confidence: 87%
“…However, three other studies reported no differences between depressed patients and controls in IBA-1-and CD68- [24], HLA-DR- [33], and CD68- [42] positive microglial density.…”
Section: Depressionmentioning
confidence: 89%